2015
DOI: 10.1021/acscatal.5b00858
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Active Phase of Heterogeneous Catalysts through In Situ Reaction Product Imaging and Multiscale Modeling

Abstract: We use multi-scale modeling to analyze laser-induced fluorescence (LIF) measurements of the CO oxidation reaction over Pd(100) at near-ambient reaction conditions. Integrating density-functional theory based kinetic Monte Carlo simulations of the active catalyst into fluid-dynamical simulations of the mass transport inside the reactor chamber we calculate the reaction product concentration directly above the catalyst surface. Comparing corresponding data calculated for different surface models against the meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 40 publications
2
46
1
1
Order By: Relevance
“…Moreover, DFT can now be linked with microkinetic models, e.g., kinetic Monte Carlo (kMC), and macroscopic gas flow computations. 17,18 The combination of all these developments leads to experiments and simulations closer to realistic catalytic conditions, while still yielding very detailed information.…”
Section: Joost W M Frenkenmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, DFT can now be linked with microkinetic models, e.g., kinetic Monte Carlo (kMC), and macroscopic gas flow computations. 17,18 The combination of all these developments leads to experiments and simulations closer to realistic catalytic conditions, while still yielding very detailed information.…”
Section: Joost W M Frenkenmentioning
confidence: 99%
“…This mechanism could be important for a working catalyst when both CO-covered, metallic regions coexist with the surface oxide as was suggested. 18,69 Parallelly, the CO flux under reaction conditions can be high enough to facilitate CO adsorption on and reaction with O atoms in the surface oxide. CO adsorption on Pd oxides was demonstrated by exposing a pre-oxidized Pd(100) surface to 0.5 hPa CO at 393 K. CO adsorption induced a change in the core-level shift of the Pd 2-fold atoms in the PdO(101) surface of the bulk oxide.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that when the reaction is in the highly active phase, under semi-realistic conditions, it is often mass transfer limited (MTL) by the ability of CO molecules diffusing and reaching onto the surface. In the MTL regime, a CO 2 boundary layer (a sharp gradient of the CO 2 cloud) is often formed at high pressure, which changes the gas composition close to the sample surface [19,20]. Blomberg et al have recently shown how this is reflected in the AP-XPS gas-phase signal by comparing gas-phase images by PLIF with AP-XPS data [21].…”
Section: Introductionmentioning
confidence: 99%
“…Zudem lohnt sich die Betrachtung der Multiskalen-Modellierung, bei der heutzutage beispielsweise quantenmechanische Betrachtungen am Katalysator mit der Strömung und Wärmeabfuhr im Reaktor simultan simuliert werden können. 64)…”
Section: Digitalisierung Der Technischen Chemieunclassified